2006
DOI: 10.5380/rf.v36i3.7519
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF INDIVIDUAL TREE DIAMETER GROWTH AND IMPLICATIONS FOR PRUNING FOR BRAZILIAN Eucalyptus grandis Hill ex Maiden

Abstract: In the present work a thinning program and a model describing dynamic of crown base recession for Eucalyptus grandis was established on an individual tree basis. Therefore, 485 trees were measured on temporary plots in forests of the companies Klabin Riocell (Guaíba), Todeschini (Cachoeira do Sul), the Federal University of Santa Maria and Aracruz Company, located in Rio Grande do Sul, Espirito Santo and Bahia, Brazil. A straight relationship between crown width and diameter at breast height (DBH) was found by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
2
10
0
14
Order By: Relevance
“…The assumption reported by Nutto (2001) and Nutto et al (2006) in studies of other species was confirmed in this study, since CA was related to DBH. Thus, the higher the predicted DBH, the greater the individual CA and the smaller the plant density supported per hectare, and vice versa.…”
Section: Dbh Growth Groupssupporting
confidence: 87%
See 1 more Smart Citation
“…The assumption reported by Nutto (2001) and Nutto et al (2006) in studies of other species was confirmed in this study, since CA was related to DBH. Thus, the higher the predicted DBH, the greater the individual CA and the smaller the plant density supported per hectare, and vice versa.…”
Section: Dbh Growth Groupssupporting
confidence: 87%
“…Thus, there is a justification for studies that evaluate crown dimensions and its implications for forest management. Nutto et al (2006) reaffirmed the importance of these types of studies, emphasizing that this type of model enables prediction of different forest management strategy scenarios, enabling quantification of thinning severity to eliminate between tree competition and maximize growth.…”
Section: Introductionmentioning
confidence: 79%
“…This means that the initial spacing will not influence overall diameter growth as long as thinning takes place at the time of canopy closure. This high initial diameter growth under low planting density is consistent with the high diameter increment potential of many Eucalyptus species of 4 to 7 cm per year in the first 3 years (Nutto et al 2006). …”
Section: Growth At the Time Of Establishmentsupporting
confidence: 78%
“…Polli (2005) constatou que, quanto mais cedo ocorrer a remoção dos galhos das árvores, mais rápida será a cicatrização do ferimento e menor será a extensão da oclusão desse ferimento. Nutto et al (2006) ressaltaram também que para a produção de madeira de Eucalyptus de alta qualidade, deve-se podar os galhos ainda vivos, o que reduz o tempo de cicatrização. Segundo O'Hara (2007) há um consenso na literatura em que a poda da floresta é mais provável que seja bem-sucedida em árvores jovens, de rápido crescimento e com ramos pequenos, o que leva a rápida oclusão e baixa probabilidade de serem infectadas por fungos.…”
Section: Extensão Da Oclusão Do Nóunclassified